One of the Rarest Syndromes in Dentistry: Gardner Syndrome - Basaran, Guvenc; Erkan, Mustafa (European Journal of Dentistry, 2008)
Gardner syndrome is a rare, autosomal dominant syndrome. It will follow a positive course with diagnosis and treatment by medical and dental specialists. Orthodontists or general dental physicians can easily diagnose the syndrome through radiological images taken in addition to dental and skeletal findings. The aim of this study was therefore to report two cases of this syndrome and to evaluate it from an orthodontic perspective in order to attract the attention of orthodontists to thisrare anomaly. (Eur J Dent 2008;2:208-212)
Keywords: Gardner syndrome; Treatment; Diagnose; Radiological evaluation